Implications and Conceptual Alternatives of Violations of Classical Assumptions in Economic Analysis - Yanuari, Cika; Putri, Maharani Avrilia Naila; Mawardani, Dhika Sekar (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research discusses the implications and conceptual alternatives related to violations of classical assumptions in economic analysis. Classical assumptions in economic analysis often simplify the complex economic reality. Violations of classical assumptions can have significant implications for understanding and predicting economic phenomena. In this study, we identify several common violations of classical assumptions, such as imperfect information, irrational behavior, and market disequilibrium. We also propose conceptual alternatives that can be used to improve the accuracy and relevance of economic analysis models to the actual economic reality. These implications and conceptual alternatives can assist economists in developing more effective and sustainable economic theories and policies.